Thermal mixing of Lake Erhai (Southwest China) induced by bottom heat transfer: Evidence based on observations and CE-QUAL-W2 model simulations - Zhao, Lei; Cheng, Sihang; Sun, Yanxin; Zou, Rui; Ma, Wenjing; Zhou, Qichao; Liu, Yong (Journal of hydrology (Amsterdam), 2021)
•Parameters affecting thermal structure were analyzed comprehensively based on a well established 2-D hydrodynamic model to explore the main process that induces the special thermal structure of Lake Erhai.•The model results revealed that the most likely process inducing the holomixis of Lake Erhai is geothermal heat transfer from sediment to water body.•Except the actual energy, approximately an additional 12% heat flux from sediment is required to mix the entire water column of Lake Erhai in summer. The thermal structure of a lake is strongly associated its hydrodynamics and climatic conditions, and is an important basis to understand the physical, chemical, and ecological processes of the lake. Lake Erhai (100°05′–100°17′N and 25°36′–25°58′E) is a large and deep lake in Yunnan Province, located on the Yunnan–Guizhou Plateau of Southwest China. Some deep lakes located in areas adjacent to Lake Erhai with similar climatic conditions and water depths are warm monomictic lakes. However, the historical data of the surface water temperature and bottom water temperature for the past 15 years (2004–2018) showed small differences (<1 °C). However, ours and some other studies on the vertical water temperature profile showed mixing of the entire water column in different seasons. We have applied a well-established hydrodynamics model (CE-QUAL-W2) to explore the main process that induces the particular thermal structure of Lake Erhai. Model calibration was conducted twice, once with the extinction coefficient (Kd) and fraction of solar radiation absorbed in the surface layer (BETA) as the main calibrated parameters, and the other considering the process of bottom-water heat exchange, represented by the sediment temperature (TSED) parameter in the CE-QUAL-W2 model. The simulation results showed that the model can reproduce water level and surface water temperature accurately with the first calibration (TSED is 14.8 °C), however, only when the TSED is greater than 24 °C, the RMSE can be less than 2 °C. The model reproduces the bottom water temperature well when the TSED value was 29.6 ± 0.37 °C. Moreover, a series of scenarios were conducted to quantify the effect of wind speed and/or tributary inflows temperature on the thermal structure of Lake Erhai, and two stability indices (Schmidt stability, Birgean work) were calculated to quantify the energy required for stratification and mixing. These results demonstrated that the most likely process to establish the holomixis of Lake Erhai is geothermal heat transfer from sediment to water column, and an additional 12% heat flux from sediment plus the actual external energy supplies from sediment are required to mix the entire water column of Lake Erhai in summer.